2018
DOI: 10.1002/esp.4347
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil factors controlling ephemeral gully erosion on agricultural fields

Abstract: The soil factor is crucial in controlling and properly modeling the initiation and development of ephemeral gullies (EGs). Usually, EG initiation has been related to various soil properties (i.e. sealing, critical shear stress, moisture, texture, etc.); meanwhile, the total growth of each EG (erosion rate) has been linked with proper soil erodibility. But, despite the studies to determine the influence of soil erodibility on (ephemeral) gully erosion, a universal approach is still lacking. This is due to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…The BSTEM uses three default coefficients for silts depending on whether they are "resistant," "moderately erodible," or "erodible," encompassing two orders of magnitude variation depending on which value is selected. Our simulated soils would be classified as "moderately erodible" based on the τ c variation after the local refinement, with values in agreement with typical agricultural soils (Knapen et al, 2007;Knapen & Poesen, 2010;Ollobarren Del Barrio et al, 2018).…”
Section: Global Sensitivity Analysissupporting
confidence: 55%
See 1 more Smart Citation
“…The BSTEM uses three default coefficients for silts depending on whether they are "resistant," "moderately erodible," or "erodible," encompassing two orders of magnitude variation depending on which value is selected. Our simulated soils would be classified as "moderately erodible" based on the τ c variation after the local refinement, with values in agreement with typical agricultural soils (Knapen et al, 2007;Knapen & Poesen, 2010;Ollobarren Del Barrio et al, 2018).…”
Section: Global Sensitivity Analysissupporting
confidence: 55%
“…There is a need to better understand when EG are filled and re-form in subsequent years in the same place, as in the study by Wilson et al (2019). For this, it seems critical to understand the impact of soil characteristics on EG erosion (Ollobarren Del Barrio et al, 2018), specifically the uncertainty associated with critical shear stress and headcut erodibility (Wilson et al, 2020).…”
Section: Global Sensitivity Analysismentioning
confidence: 99%
“…Assuming that the gully material to be eroded is composed primarily of cohesive and non‐cohesive clastic sediment, the controlling parameters that could affect k d and τ c can include physical, geochemical, and biological properties as well as land management practices (Knapen et al, ; Grabowski et al, ), all of which can depend on time. For agricultural landscapes, functional relationships to predict the entrainment of soils typically include texture (sand, silt, and clay content), soil chemistry (concentrations of Na, K, Ca, and Fe and organic content), bulk density, and/or water content (Bryan, ; Römkens et al, ; Gilley et al, ; Liu et al, ; see reviews in Clark and Wynn, ; Ollobarren Del Barrio et al ., ; Su et al, ). Moreover, soil detachment may also depend upon the erosive forces applied (Rose, , ; Park et al, ; Nearing et al, ), and subsurface hydrologic conditions including piping (Tanaka, ; Huang and Laflen, ; Römkens et al, ; Bernatek‐Jakiel et al, ; Wilson et al, ).…”
Section: The Global Impact Of Gully Erosion and The Urgency For Technmentioning
confidence: 99%
“…The average EG width-depth ratio varied in the range of 1.13-1.83 in our study, which was similar to the results reported for the Loess Pla- was applied in our study compared with that of , which restricted concentrated flow incision within the EG (Bennett et al, 2000) and resulted in higher width-width ratios. However, torrid red soil with a higher clay content and black soil with higher clay and organic contents than loess soil may play a crucial role in restricting EG flow incision (Ollobarren et al, 2018) and contribute to much higher width-depth ratios.…”
Section: Eg Morphology On Steep Loessial Slopesmentioning
confidence: 99%